(untitled) (Praxis Educativa, 2012)
The topic on teacher training is so generic that it has turned out to be almost oceanic. For centuries universities have not shown much concern about what at present is known as university pedagogy. For some experts pedagogical training has been of outmost relevance, while for others it is a secondary issue. In our opinion, in order to analyse training, three great historical periods which have changed university teaching from conceptions which are rather debatable have to be considered: encyclopaedism, didactism and technology and their bureaucratic characteristics. Whatever curricular model is implemented in teacher training, there are three fundamental issues to be taken into account: work Planning; Management to create and recreate adequately the cultural reality data that teachers meet; Evaluation of learning as such, of complementary work in and out of the classroom, as well as innovations and the good or bad disposition by means of which we get acquainted with other people.